2010
DOI: 10.1016/j.compscitech.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and post-fatigue tensile behaviour of non-crimp stitched and unstitched carbon/epoxy composites

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.submitted to Composites Science and Technology 1 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…There are two main types of 3D woven composites: interlock fabric, where the z-binder is interlaced with the in-plane yarns, and orthogonal fabric, where the z-binder holds in place the entire stack of 2D fabrics, thus avoiding crimp and maximising the in-plane stiffness [139]. Carvelli et al [147] showed that there is a dependency of these composites on the loading direction (when comparing 2D and 3D wovens) [0, 90] s orthogonal CFRP in both warp and weft directions and tested in (T-T) fatigue. The fatigue performance of the 2D samples were in between weft (lower) and warp (higher), although the difference was marginal, especially when considering the propensity for scatter when it comes to fatigue of CFRP.…”
Section: Effect Of Fibre Architecture On the Fatigue Properties -2d Cmentioning
confidence: 99%
“…There are two main types of 3D woven composites: interlock fabric, where the z-binder is interlaced with the in-plane yarns, and orthogonal fabric, where the z-binder holds in place the entire stack of 2D fabrics, thus avoiding crimp and maximising the in-plane stiffness [139]. Carvelli et al [147] showed that there is a dependency of these composites on the loading direction (when comparing 2D and 3D wovens) [0, 90] s orthogonal CFRP in both warp and weft directions and tested in (T-T) fatigue. The fatigue performance of the 2D samples were in between weft (lower) and warp (higher), although the difference was marginal, especially when considering the propensity for scatter when it comes to fatigue of CFRP.…”
Section: Effect Of Fibre Architecture On the Fatigue Properties -2d Cmentioning
confidence: 99%
“…His researches devoted to the fatigue behavior of long fiber reinforced composites were mainly dedicated to: non-crimp fabrics, 97,160163 2 D textiles 85,86,164,165 and 3 D reinforcements. 134,166,167…”
Section: Fatigue Of Compositesmentioning
confidence: 99%
“…The stiffness and strength of laminates loaded in quasi-static tension can be unaffected, increase or more common reduced by stitching [11,12]. The characteristics of fatigue and post-fatigue behavior have been investigated [13], and the impact and post-impact properties for NCF composites have been estimated [14].…”
Section: Introductionmentioning
confidence: 99%